Line Laser as an Assistance for Facial and Dental Midlines Evaluation in Single-Splint Orthognathic Surgery. Issue 7 (October 2017) - Yu, Chung-Chih; Chen, Yu-Ray; Lin, James Cheng-Yi
Abstract : Abstract: Coincidence of facial and dental midlines is one of the important goals in orthognathic-orthodontic treatment to achieve optimum facial aesthetics and good occlusal functions. Tools assisting diagnosis of facial midline are usually ruler or dental floss. These tools are usually hand held and hinder the global sight required in facial evaluation. Line laser device projects a steady narrow laser line and is commonly used in construction and carpentry to replace traditional chalk line tool. The authors take the advantages of line laser and incorporate it into facial evaluation in the authors' practice of single-splint orthognathic surgery. During June 2013 to May 2015, the authors used line laser device to evaluate facial and dental midlines in 28 patients of facial asymmetry requiring orthognathic surgery during consultation in office and intraoperative evaluation. The details of integrating this device to practice are described. All the patients showed improved facial symmetry and coincidence of facial and dental midlines after operation. Postoperative orthodontics were finished smoothly. Line laser is available from general utility stores and is safe to use according to laser safety regulation. From the authors' experiences, it is burden free to apply in facial and dental midlines evaluation and improves the practice.